1996
DOI: 10.1021/bi952168g
|View full text |Cite
|
Sign up to set email alerts
|

The Immunosuppressive Metabolite of Leflunomide Is a Potent Inhibitor of Human Dihydroorotate Dehydrogenase

Abstract: The active metabolite of leflunomide. A771726, is a novel immunosuppressive compound that has been shown to be a powerful antiproliferative agent for mononuclear and T-cells. The molecular mechanism of action for this compound has not been clearly established. In vitro cellular and enzymatic assays, however, demonstrate that leflunomide is an inhibitor of several protein tyrosine kinases, with IC50 values between 30 and 100 microM. The in vivo properties of A771726 are reminiscent of another immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
150
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(151 citation statements)
references
References 11 publications
1
150
0
Order By: Relevance
“…It has been suggested that the effects of methotrexate on the production of tissue-degrading factors are related to adenosine receptor stimulation (52) rather than to the effects on folate metabolism (53). The primary mode of action of leflunomide is thought to be inhibition of pyrimidine biosynthesis (21,(53)(54)(55)(56)(57), but other mechanisms are involved as well (22,24,58,59). Direct cell-cell contact between activated T cells and monocytes might be involved in MMP-1 induction (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the effects of methotrexate on the production of tissue-degrading factors are related to adenosine receptor stimulation (52) rather than to the effects on folate metabolism (53). The primary mode of action of leflunomide is thought to be inhibition of pyrimidine biosynthesis (21,(53)(54)(55)(56)(57), but other mechanisms are involved as well (22,24,58,59). Direct cell-cell contact between activated T cells and monocytes might be involved in MMP-1 induction (60).…”
Section: Discussionmentioning
confidence: 99%
“…Leflunomide is a prodrug that is rapidly converted in the cell into the active metabolite A77 1726. Leflunomide exerts its effects by various mechanisms; the proposed primary mode of action in RA is inhibition of the enzyme dihydroorotate dehydrogenase (19)(20)(21). Leflunomide also interferes with the phosphorylation of tyrosine kinases, resulting in effects on signal transduction pathways (22)(23)(24).…”
mentioning
confidence: 99%
“…Leflunomide specifically inhibits the activity of dihydro-orotate dehydrogenase (DHODH) in a non-competitive manner. 1 DHODH is the rate-limiting enzyme in the de novo biosynthesis of pyrimidines. While its antiproliferative effect on lymphocytes and mononuclear cells is completely reversible by exogenous uridine, blockade of DHODH is considered to be the main mode of action.…”
Section: The Immunomodulatory Drug Leflunomide Inhibits Cell Cycle Prmentioning
confidence: 99%
“…The primary mode of action is thought to be selective inhibition of de novo pyrimidine synthesis by blocking the rate-limiting enzyme dihydroorotate dehydrogenase (4). Activated CD4ϩ T cells proliferate rapidly during the progression of RA, a process involving de novo pyrimidine synthesis (5).…”
mentioning
confidence: 99%